PHYSICOCHEMICAL CHARACTERIZATION AND SENSORY ANALYSIS OF JAMS PRODUCED FROM OPUNTIA FICUS-INDICA CLADODES - KAMAL, LEGRINE; DJAHIDA, BENAOUANA; DALILA, ABDESSEMED (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study focuses on the production and evaluation of the physicochemical and sensory qualities of two jams, J1 and J2, produced from Opuntia ficus-indica cladodes. J1 made from cladodes with the addition of lemon juice and J2 made from cladodes with added 1/3 orange pulp and lemon juice. Methods: The moisture content is determined by drying the fresh cladodes in an oven at 103°C. The soluble solids content is determined by measuring the Brix at 20°C using a digital refractometer. Total soluble sugar content was examined using the phenol-sulfuric acid colorimetric method using a spectrophotometer ultraviolet (UV)-visible spectroscopy. Sensory evaluation was carried out by 20 panelists. The individual quality features were evaluated using significance factors: Color, texture, aroma, and taste. For instrumental color analysis, the measurement was carried out with the use of spectrophotometer UV-visible, the results were expressed using the CIE (L*, a*, and b*) system. Results: The physical and chemical analysis results give fairly appreciably results on average for total sugars (55.4 and 58.76%), Brix (65 and 67%), humidity (29.79 and 29.89%), and acidity (0.45 and 0.48 g/100 g). The sensory results give for color (3.73 and 6.42), for taste (4.89 and 5.21), for odor (3.00 and 3.57), and texture (4.21 and 4.21). The physicochemical analyses for cladodes showed a rich content for water 92.74, the total sugar content is 5.53. Conclusion: These elaborate jams meet the accepted international standards for jams. The sensory evaluation revealed that J2 was the most appreciate in terms of color, odor, texture, and taste.